2005
DOI: 10.1111/j.1440-1746.2005.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cagA+ and cagA– strains of Helicobacter pylori on the human gastric mucus layer thickness

Abstract: The human gastric mucus thickness is not affected by infection with cagA+ or cagA- strains of H. pylori compared with uninfected. Although a trend of increased mucus thickness with cagA+ infection was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…In a study by Lindahl et al, characterizing aspirated gastric fluids from healthy volunteers, no genderrelated differences in electrolyte concentrations, osmolality, bile salt concentrations and protein content between men and women were observed (Lindahl et al, 1997). Furthermore, Al-Marhoon et al reported similar mean mucus layer thickness when comparing men to women (55.5 ± 1.1 vs. 48.2 ± 1.1 µm, respectively) (Al-Marhoon et al, 2005). Although literature reports on gender-related differences remain scarce, this study suggests that gender most likely does not influence mucus layer thickness.…”
Section: Gender and Racesupporting
confidence: 53%
See 2 more Smart Citations
“…In a study by Lindahl et al, characterizing aspirated gastric fluids from healthy volunteers, no genderrelated differences in electrolyte concentrations, osmolality, bile salt concentrations and protein content between men and women were observed (Lindahl et al, 1997). Furthermore, Al-Marhoon et al reported similar mean mucus layer thickness when comparing men to women (55.5 ± 1.1 vs. 48.2 ± 1.1 µm, respectively) (Al-Marhoon et al, 2005). Although literature reports on gender-related differences remain scarce, this study suggests that gender most likely does not influence mucus layer thickness.…”
Section: Gender and Racesupporting
confidence: 53%
“…Although no age-related changes in mucus layer thickness were observed in H. pylori negative subjects, mucus layer thickness was found to significantly decrease with age in H. pylori positive subjects (Newton et al, 2000). Again, it may be hypothesized that this change might be due to a higher prevalence of gastric atrophy and gastritis in elderly subjects as a result of long-time infection with H. pylori (Al-Marhoon et al, 2005;Newton et al, 2000). Lastly, Feldman et al investigated changes in basal and peak pepsin output (BPO/PPO) in relation to age.…”
Section: Ageelderlymentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the expression patterns of gastric mucins MUC5AC and MUC6 seem to be altered in H. pylori-infected patients and skewed toward more MUC6 (5,37). Measurements of mucus thickness in biopsies have shown both a decreased mucus thickness in H. pylori-positive subjects (27,31) as well as no difference in mucus thickness between H. pylori-positive and -negative subjects (1,2,24,25). The present study is the only study presenting mucus thickness values from in vivo measurements including the accumulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Once adhering to the gastric mucosa the bacteria can freely divide, so that within 3 days they cover the gastric epithelial surface and penetrate the gastric glands. Most interesting is the extreme thickness of the mucus layer, which is normally approximately 50–170 µ thick [23], i.e. 10–20 epithelial cell depths.…”
Section: Unique Relationship Between H Pylori and The Gastric Mucosamentioning
confidence: 99%